Wavelength Tuning for LiNbO3 Photonic Sensor to Have Linear Operation Point. Issue 10 (26th July 2013) - Zhang, Jiahong; Chen, Fushen; Sun, Bao; Li, Chengxin
ABSTRACT A new method to control the bias angle of asymmetric Mach–Zehnder interferometer‐based LiNbO3 photonic sensor for accurate intensive E‐field measurement has been proposed and experimentally demonstrated in this article. By adjusting the wavelength of a tunable laser using a microcontroller unit, the sensors can have a linear operating point while not distort the E‐field under measurement. This method successfully controls such LiNbO3 photonic sensor without distorting the output optical waveform. Linear characteristic of this sensing system with proposed control system has been measured and the correlation coefficient between measured and fitting is 0.999 from 160 to 840 Kv/m. All these prove wavelength tuning is available for photonic sensors to detected and extract E‐field accurately. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2326–2329, 2013